Preparation of AgInS2/TiO2 composites for enhanced photocatalytic degradation of gaseous o-dichlorobenzene under visible light - Liu, B.; Li, Xin Yong; Zhao, Q.; Ke, J.; Tadé, Moses; Liu, S. (2016)
In this work, the TiO2 and AgInS2 heterostructures with different mole ratios were prepared through a simple hydrothermal method. The as-synthesized composites were characterized by field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). The results showed that the obtained materials exhibited multi-heterostructures, possessing the orthorhombic phase of AgInS2, and anatase and rutile phase of TiO2. Furthermore, the optical properties displayed that a series of AgInS2/TiO2 composites could expand the visible-light response range and enhance the absorption intensity by UV–vis diffuse reflection spectroscopy (DRS). The photo-generated carriers were subsequently investigated by the surface photovoltage (SPV) spectra and photoluminescence (PL) technique, and the results demonstrated that the forming heterojunctions greatly depressed the recombination of photogenerated charges in the composites. Finally, the materials were tested as photocatalysts for degradation of gaseous 1, 2-dichlorobenzene (o-DCB) under visible-light irradiation, and the degradation process and final products (CO2) were identified by using in situ Fourier transform infrared (FTIR) spectroscopy. The mechanism of enhanced photocatalytic activity was proposed in terms of the quantum calculation of AgInS2 and the proper band alignment of AgInS2/TiO2 composites.